Cnidium dubium (Schkuhr) Thell.: distribution in Romania, ecology and sociology. - Danciu, Marius; Indreica, Adrian; Bacaintan, Nicolae (Babes-Bolyai University Cluj-Napoca, 2009)
Cnidium dubium (Apiaceae), a species with ecological preferences for flooded meadows, is affected by the contraction of this habitat throughout Europe, because of the construction of dykes along rivers. In Romania too, this species is very rare and some literature data on its distribution need to be critically verified. Studies of the ecology and phytosociology of Cnidium dubium were carried out in a site on meadows of the Râul Negru (central compartment of the Braşov Depression), where a large population was identified. The affinities of the species for phytocoenoses dominated by Deschampsia cespitosa (Cnidio-Deschampsietum association) and developed on soils rich in uninflatable clay (pelosol) are quite obvious. The meadows of Cnidium dubium and Deschampsia cespitosa are located especially in the north-eastern part of Central Europe, but in Romania they had not been reported until now. In Romania, as well as in the Braşov Depression, another phytocoenosis of the association is reported from the Ciuc Depression, in the Olt floodplain
Keywords: Cnidium dubium; Cnidio-Deschampsietum; priority habitats; meadow vegetation; 6440 habitat